Learning Style Preferences, Study Habits, and Academic Performance in Mathematics: Perspectives of Freshmen College Students amidst the COVID-19 Pandemic - Cuizon, Kate Angelli D.; de Luna, Fiona Ysabella Z.; Natividad, Anne Gwyneth E.; Ortiz, Justine Z.; Osorio, Lynie V.; Juan, Kyla Bianca T. San; Punzalan, Christopher Habunatalia (Universitas Terbuka, 2022)
Students can attain higher academic comprehension and performance by using instructional tactics and approaches that naturally match their interests. Researchers investigated potential learning gaps that could occur due to disparities in students' learning abilities. As a result, this study determined students' preferred learning styles, study habits, and academic achievement in mathematics as a general education course. A total of 100 freshmen college students were non-randomly recruited for this study, which used a quantitative descriptive approach. The study adopted the Reid Perceptual Learning Style Questionnaire and Gilbert Wrenn's Inventory of Study Habits as tools for data collection. Furthermore, descriptive statistics such as mean, ANOVA, and Post-hoc Tukey HSD Test were used to investigate freshmen college students' preferred learning styles, study habits, and academic performance in mathematics. The survey's findings revealed that students favor the tactile, group, and individual learning styles as minor learning modes, despite having poor study habits. A high level of academic achievement was also revealed. Gender and course caused significant disparities in their study habits, according to a test of difference. When categorized by profile factors, no significant variations in learning styles or academic achievement were discovered. The study's recommendations can help teachers and future researchers develop and implement educational interventions.